Developing a spiritual care competency framework for pre-registration nurses and midwives. (October 2019) - Attard, Dr Josephine; Ross, Dr Linda; Weeks, Keith W.
Abstract: This paper identifies competencies in spiritual care from an in-depth literature review and develops a theoretical framework for competencies in spiritual care. It forms part of a larger modified Delphi study which recruited international nursing/midwifery experts. Using Braun and Clark (2006) adapted six-phase content thematic analysis, 7 domains and 116 competency items were generated from an in-depth literature review in three areas; spirituality and spiritual care, spiritual care education, and spiritual care curricular contents.